2015
DOI: 10.4103/0976-237x.161860
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of four different techniques in removing intracanal medicament from the root canals: An in vitrostudy

Abstract: Aim:To evaluate the effectiveness of different techniques in removing calcium hydroxide (Ca(OH)2) from the root canal.Materials and Methods:Twenty-four freshly extracted mandibular premolars were instrumented using ProTaper rotary instruments. The teeth were longitudinally split into two halves, cleaned of debris. The two halves were then reassembled and filled with Ca(OH)2 and were divided into four groups. In Group I, the teeth were irrigated with 5 mL of 2.5% sodium hypochlorite (NaOCl) and 5 mL of 17% of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…To our knowledge, no study has compared the effectiveness of CanalBrush on the removal of antibiotic pastes. However, a recent study reported that no significant difference was found between CanalBrush and PUI on the removal of CH from root canal surfaces 7 . On the other hand, Grischke, et al 13 (2014) investigated the efficacy of four different irrigation systems in removing root canal sealer from simulated irregularities on the root canal wall, and reported that PUI is more effective than CanalBrush.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has compared the effectiveness of CanalBrush on the removal of antibiotic pastes. However, a recent study reported that no significant difference was found between CanalBrush and PUI on the removal of CH from root canal surfaces 7 . On the other hand, Grischke, et al 13 (2014) investigated the efficacy of four different irrigation systems in removing root canal sealer from simulated irregularities on the root canal wall, and reported that PUI is more effective than CanalBrush.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning 1 st and 2 nd group, conventional and ultrasonic technique, there was not statistically significant difference. That comes in disagreement with some authors[ 21 ] who compared the efficacy of conventional technique and passive ultrasonic irrigation for the removal of calcium hydroxide. They found that ultrasonic agitation of NaOCl was significantly more effective than irrigant-only techniques.…”
Section: Discussionmentioning
confidence: 76%
“…Myriad of studies have calculated and reported the remaining amount of Ca(OH) 2 on the canal walls using various methods, such as micro-computed tomography, CBCT, stereo microscopes and scanning electron microscopes ( 23 , 25 , 27 , 38 ), but all of them were on extracted teeth which fails to mimic the conditions that exist in oral environment. This trial compares two techniques for removal of intracanal medicament in clinical setup so that the generated results are practical and applicable for clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated by sample size calculator (sample size determination in Health studies, WHO). The study by Bhuyan et al ( 25 ) reported that the mean percentage of remaining Ca(OH) 2 after using ProTaper rotary was 35.49±4.73 while after using ultrasonic activation the mean remaining percentage of Ca(OH) 2 was 25.82±6.72. Keeping the above difference at the level of significance (α) at 1% and power of study (1-β) at 99%, we needed at least 21 observations per group.…”
Section: Methodsmentioning
confidence: 99%